Le rôle de l'information en droit des entreprises en difficulté - Ould Eba, Moussa (Université Toulouse 1 Capitole, 2013)
L’information est un moyen de gestion fiable et une garantie indispensable pour la protection des intérêts des acteurs de l’activité économique. Elle joue un rôle important dans la prévention et le traitement des difficultés des entreprises. En effet, à la lumière des informations comptables, financières et sociales, les dirigeants peuvent prévenir les difficultés et prendre les décisions adaptées à la situation de l’entreprise. Toutefois, en cas de procédures collectives, le besoin de protection se substitue à celui de prévention. Le rôle de l’information est dès lors de garantir le bon déroulement de la procédure collective et d’assurer la protection des intérêts des parties.
Keywords: Entreprises en difficulté; Information prévisionnelle; Publicité -- Droit; Secret professionnel

Le juge et le sauvetage de l'entreprise en difficulté en droit OHADA et en droit français : étude de droit comparé - Balemaken, Eugène Louis René (Université Paris 2, 2013)
L’Acte uniforme portant organisation des procédures collectives d’apurement du passif, adopté le 10 avril 1998 à Libreville et entré en vigueur le 1er janvier 1998 est venu harmoniser le droit de la faillite dans les pays membres de l’Organisation pour l’Harmonisation en Afrique du droit des Affaires (OHADA). En effet, ces pays étaient jusque là, en la matière, dotés de textes inadaptés datant de l’époque coloniale. Au regard de la parenté aujourd’hui avérée des ordres juridiques africain et français en Droit des entreprises en difficulté, il n’était pas inintéressant de mener une étude comparative sur le rôle du juge dans le sauvetage de l’entreprise en difficulté dans les deux systèmes. L’étude révèle qu’en droit africain et en droit français, les degrés d’intervention du juge varient selon que l’entreprise est in bonis ou selon qu’elle est en état de cessation des paiements. Pour permettre au juge de mener à bien la mission de sauvetage de l’entreprise en difficulté, les législateurs africain et français lui ont octroyé des moyens d’action processuels qui se caractérisent de manière tantôt convergente et tantôt divergente selon les cas, par une maîtrise de l’instance et, par l’exécution immédiate des décisions judiciaires rendues. L’étude révèle cependant l’existence dans les deux ordres juridiques de nombreux obstacles qui s’opposent à la mission de sauvetage incombant aux juges africain et français, obstacles tant d’ordre fonctionnel que d’ordre structurel. A côté des solutions apportées ici et là à toutes ces problématiques, et à bien d’autres soulevées tout au long de l’étude, de nouvelles propositions sont faites pour rendre l’action du juge plus efficiente. Il reste que, qu’il s’agisse du droit africain ou du droit français, à travers la question relative au rôle du juge dans le sauvetage de l’entreprise en difficulté, se pose la récurrente problématique de la réelle capacité du droit à juguler les phénomènes économiques. = The Uniform Act organizing collective proceedings for discharge of liabilities, adopted on 10 April 1998 in Libreville and entered into force on 1 January 1998 came harmonize the insolvency law in the Member countries of the Organization for the Harmonization of the law of Affairs (OHADA). Indeed, these countries were up there, in material, with inadequate texts dating from the colonial era. Under today proven relatives of African and French legal systems in law firms in difficulty, it was interesting to carry out a comparative study on the role of the judge in the rescue of the firm in difficulty in both systems. The study reveals that African law and French law, judge's intervention levels vary depending on whether the company is in bonuses or depending on whether it is in a State of cessation of payments. To enable the judge to carry out the mission to rescue of the firm in difficulty, African and French lawmakers have granted action procedural means characterized sometimes convergent and sometimes divergent manner as appropriate, by a master of the instance and immediate execution of judicial decisions. However, the study reveals the existence in both legal orders of many obstacles that oppose the incumbent judges African and French, rescue mission obstacles so many functional order than structural. Next to the solutions here and all these problems, there other proposals are made to make more efficient action by the judge. It remains that, whether it's African law or French law, through the question of the role of the judge in the rescue of the firm in difficulty, arises the recurring problem of the real capacity of the law to curb economic phenomena.
Keywords: Access to the Courts; Accès au juge; Africa; Afrique; Entreprise en difficulté; France; Independance and impartiality of the judge; Indépendance et impartialité du juge; Intervention judiciaire; Judicial intervention; Juridicisation - Afrique; Juridicisation - France; OHADA; Procédures collectives; Redressement d'entreprise; Rescue of the undertaking; Sauvetage de l'entreprise; Specialization of justice; Stay of proceedings

La prévention des difficultés des entreprises : étude comparative entre le droit français et le droit marocain - Lyazami, Nahid (Université de Toulon, 2013)
Le traitement préventif et amiable des difficultés des entreprises est la solution idoine pour préserver des entreprises viables, apurer le passif et sauvegarder les emplois. Le législateur français, à travers la mise en place d’un arsenal juridique qui favorise le traitement précoce des difficultés des entreprises, a pu faire un pas géant vers la dissipation et l’éclipse de l’esprit répressif et pénal au profit des mesures de prévention et de réparation des dommages. Cette nouvelle conception de réaction prompte contre les difficultés des entreprises a trouvé un véritable engouement auprès du législateur marocain. The precautionary and amicable treatment of difficulties of firms is suitable resolution to preserve viable firms, audit debit and safeguard jobs. The French legislator, across the installation of a juridical armory which favours the precocious treatment of difficulties of firms, could make a huge step towards clearing up and eclipse of repressive and criminal mind to the advantage of the measurements of prevention and repairing of successive damage in said difficulties. This new comprehension of prompt reaction against difficulties of firms found a true infatuation to the Moroccan legislator.
Keywords: Conciliation; Difficulties of firms; Difficultés des entreprises; Entreprises en difficulté; France; Maintenance; Maroc; Médiation financière; Prevention; Prévention; Reconciliation; Redressement d'entreprise; Sauvegarde; Étude comparative

Development of a uniform insolvency law in SADC : lessons from OHADA - Leno, Ngaundje Doris (Journal of African Law, 2013)
This article argues that, with the global or cross-border nature of many corporate activities, there is an increasing need for a uniform insolvency law approach to the financial distress of a corporation in the Southern African Development Community. In doing so, the article highlights lessons the community may learn from the Insolvency Act of the Organisation for the Harmonization of Business Law in Africa. Emphasis is given to that organization’s success in developing a uniform insolvency act (ie one which is directly applicable in its contracting states). The article also proposes a number of recommendations.
Keywords: Africa; Bankruptcy; Business law; Financial distress; Insolvency Act; Insolvency law

Corporate Restructurings in Zimbabwe : a Legal Analysis of the Regulation of Corporate Mergers and Acquisitions in Zimbabwe - Nzero, Ignatious (University of Pretoria, 2013)
The Zimbabwean economy rapidly declined over the past two decades. A record hyperinflationary environment and a collapse of the financial service sector coupled by lack of external lines of credit created a difficult operating environment for corporate businesses. Businesses thus either closed down operations or resorted to survival strategies. Corporate mergers and acquisitions emerged as natural favoured strategies in implementing survival corporate restructuring transactions. However, the success of such strategies largely depends on the effectiveness of the merger regulatory framework, that is, its ability to promote beneficial corporate restructuring transactions on one hand and to maintain the competitive structure of the market on the other hand. This research analyses the current merger regulatory framework in Zimbabwe and assesses whether it is suited to promote beneficial corporate restructuring transactions implemented through mergers and acquisitions without unnecessarily distorting the competitive structure of the market. Employing the failing firm doctrine as the focal point, the research identified a number of shortcomings within the current merger regulatory framework that impacts upon its ability to effectively promote beneficial corporate mergers and acquisitions without sacrificing the competitive market structure. Selected comparative jurisdictions were used to draw various lessons for Zimbabwe. The aim of the comparative study was not to provide an exhaustive analysis of these jurisdictions but to identify specific arrears that can be used to develop and suggest an effective merger regulatory framework for Zimbabwe. In order to remedy the identified shortcomings inherent within the current Zimbabwean merger regulatory framework, this thesis proposes a number of amendments to the current Competition Act [Chapter 7:01] of 1996. These proposed amendments are aimed at bringing clarity, flexibility and strengthening the merger regulatory framework including the institutions tasked with such. The research is primarily a legal analysis of the Zimbabwean merger regulating statute and its implications on any decisions made by the competition authority. As such, the thesis states the status of legal development in Zimbabwe and the selected comparative jurisdictions as of 31 July 2013.